Multipronged interventions to reduce surgical site infections: A multicenter implementation research protocol. - Rachna Rohilla; Mayank Gupta; Thekkumkara Surendran Anish; Jerin Jose Cherian; Mahendra Pratap Singh; Ashish Kumar Kakkar; Aparna Mukherjee; Niti Mittal; Sandeep Kaushal; Devi Vijay; Robin Kaushik; Syed Shariq Naeem; et al. (PLoS ONE)
Background Surgical site infections (SSIs) are a major yet preventable cause of poor post-operative clinical outcomes, prolonged ICU/hospital stay, increased antibiotic consumption and added cost of therapy. Low- and Middle-income Countries (LMICs) have disproportionately higher rates of SSIs as compared to high-income countries despite various national and international guidelines in place as multipronged, combined interventions are seldom used. The IMPRESS project aims to respond to this urgent need to identify and evaluate the quality improvement measures contextualized to the logistic constraints of LMIC settings such as India. Methods and analysis We adopt a multi-center longitudinal mixed-methods study to be conducted over a period of 2 years in various phases. Phase 1 will be formative research with the objective of identifying knowledge gaps and baseline data collection. Phase II will involve co-development of multipronged interventions addressing identified barriers. Phase III will focus on the deployment of the selected multipronged interventions. Phase IV will be the post-intervention phase to evaluate the impact of the interventions. The study has been prospectively registered with CTRI and is supported by a funding grant from the Indian Council of Medical Research, New Delhi. The Institutional Ethics Committee approval has been obtained from all the sites involved in the study.